Vanadium(V) Removal from Aqueous Solutions and Real Wastewaters onto Anion Exchangers and Lewatit AF5 - Anna Wołowicz; Zbigniew Hubicki (Molecules, 2022)
Adsorption abilities of weakly (Purolite A830), weakly basic/chelating (Purolite S984), and strongly basic (Lewatit MonoPlus SR7, Purolite A400TL, Dowex PSR2, Dowex PSR3) ion exchange resins of different functional groups and microporous Lewatit AF5 without functional groups towards vanadium(V) ions were studied in batch and column systems. In the batch system, the influence of the sorbent mass (0.01–0.1 g), pH (2–10), the phase contact time (1–1440 min),and the initial concentration (5–2000 mg/L) were studied, whereas in the column system, the initial concentrations (50, 100, and 200 mg/L) with the same bed volume and flow rate (0.4 mL/min) were studied. Desorption agents HCl and NaOH of 0.1–1 mol/L concentration were used for loaded sorbent regeneration. The pseudo-first order, pseudo-second order and intraparticle diffusion kinetic models as well as the Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherm models were used to describe kinetic and equilibrium data to acquire improved knowledge on the adsorption mechanism. The desorption efficiency was the largest using 0.5 mol/L NaOH for all sorbents under discussion. Purolite S984, Purolite A830, and Purolite A400TL, especially Purolite S984, are characterized by the best removal ability towards vanadium(V) from both model and real wastewater.